4-aminopyridyl-based lead compounds targeting CYP51 prevent spontaneous parasite relapse in a chronic model and improve cardiac pathology in an acute model of Trypanosoma cruzi infection. - Claudia Magalhaes Calvet; Jun Yong Choi; Diane Thomas; Brian Suzuki; Ken Hirata; Sharon Lostracco-Johnson; Liliane Batista de Mesquita; Alanderson Nogueira; Marcelo Meuser-Batista; Tatiana Araujo Silva; Jair Lage Siqueira-Neto; William R Roush; et al. (Public Library of Science (PLoS), 2017)
Chagas disease, caused by the protozoan Trypanosoma cruzi, is the leading cause of heart failure in Latin America. The clinical treatment of Chagas disease is limited to two 60 year-old drugs, nifurtimox and benznidazole, that have variable efficacy against different strains of the parasite and may lead to severe side effects. CYP51 is an enzyme in the sterol biosynthesis pathway that has been exploited for the development of therapeutics for fungal and parasitic infections. In a target-based drug discovery program guided by x-ray crystallography, we identified the 4-aminopyridyl-based series of CYP51 inhibitors as being efficacious versus T.cruzi in vitro; two of the most potent leads, 9 and 12, have now been evaluated for toxicity and efficacy in mice.Both acute and chronic animal models infected with wild type or transgenic T. cruzi strains were evaluated. There was no evidence of toxicity in the 28-day dosing study of uninfected animals, as judged by the monitoring of multiple serum and histological parameters. In two acute models of Chagas disease, 9 and 12 drastically reduced parasitemia, increased survival of mice, and prevented liver and heart injury. None of the compounds produced long term sterile cure. In the less severe acute model using the transgenic CL-Brenner strain of T.cruzi, parasitemia relapsed upon drug withdrawal. In the chronic model, parasitemia fell to a background level and, as evidenced by the bioluminescence detection of T. cruzi expressing the red-shifted luciferase marker, mice remained negative for 4 weeks after drug withdrawal. Two immunosuppression cycles with cyclophosphamide were required to re-activate the parasites. Although no sterile cure was achieved, the suppression of parasitemia in acutely infected mice resulted in drastically reduced inflammation in the heart.The positive outcomes achieved in the absence of sterile cure suggest that the target product profile in anti-Chagasic drug discovery should be revised in favor of safe re-administration of the medication during the lifespan of a Chagas disease patient. A medication that reduces parasite burden may halt or slow progression of cardiomyopathy and therefore improve both life expectancy and quality of life.